Pollution by Takeaways Shops: Implementation of Ecofriendly Food Containers in Paraná - Cruzado, Nahuel; Miño, Agustín (My University, 2022)
Summary: Paraná, Entre Ríos is a city whose number of residents grows every day. People have moved to this city to work and study so they usually have little time to cook every day. This busy lifestyle causes that people decide to buy food instead of cooking it. This demand of ready-to-eat food generates contamination by the materials used for wrapping and delivering it. The purpose of this work is to discuss the problem of the pollution by the containers that takeaways or restaurants use to sell their food. Also, a solution to this problem will be addressed. Resumen: Paraná es una ciudad cuyo número de residentes crece cada día. Las personas se han mudado a esta ciudad para trabajar y estudiar, por lo que suelen tener poco tiempo para cocinar a diario. Este estilo de vida ocupado provoca que las personas decidan comprar comida en lugar de cocinarla. Esta demanda de comida lista para comer genera contaminación debido a los materiales utilizados para envolver y entregarla. El propósito de este trabajo es discutir el problema de la contaminación causada por los envases que utilizan los restaurantes para vender su comida para llevar. Además, se abordará una solución para este problema.
Keywords: Inglés I; plastic containers contamination; ecofriendly food containers; contaminación por envases de plásticos; recipientes ecológicos para comida